System reliability optimization for an assembly line under uncertain random environment. (August 2020) - Li, Yuchen; Peng, Rui; Kucukkoc, Ibrahim; Tang, Xiaowen; Wei, Fang
Highlights: A new reliability metric of assembly line is provided to capture two kinds of task time uncertainties. A multi-objective mathematical model considering both efficiency and reliability measures is formulated. Two neighborhood search methods with different restart mechanisms are developed to solve the pro-posed problem. Abstract: An assembly line is an industrial arrangement of machines, equipments and operators for continuous flow of work-pieces in mass-production operations. Recently, the reliability of assembly production has been investigated by taking into account task time uncertainties. This paper provides a new reliability metric which encompasses two types of task time uncertainties. A multi-objective mathematical model was developed to maximize the reliability and efficiency of assembly lines. Neighborhood search methods with two restart mechanisms are devised to solve the model and they are compared in a numerical study. Further, the results show some managerial implications for the production planners. The methodology proposed in this research can be applied to many industries when some historical data of uncertain inputs are available and some are not.